A laminated composite electrolyte with interface optimization function and preparation method thereof
By using a silane coupling agent containing acrylamide groups in all-solid lithium batteries to combine with organic and inorganic electrolytes, a bonding interface is formed and the diffusion of lithium ions is regulated, the interface problem in the battery is solved and the battery performance and cycle life is improved.
Patent Information
- Application Number
- CN202210477425.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-04
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2042-05-04
AI Technical Summary
In all-solid-state lithium batteries, the interface problems between the positive and negative electrode materials and the hard oxide electrolyte lead to poor solid-solid contact, stress/strain changes, crack formation and expansion, interface layering, and physical connectivity reduction, affecting battery performance.
A silane coupling agent containing acrylamide groups is used to combine with organic electrolytes and inorganic electrolytes to form a bonding interface through chemical interactions, adjust the organic/inorganic interface, reduce the internal resistance of the interface, and use multiple hydrogen bonds and acyloxy groups of acrylamide groups to regulate the diffusion behavior of lithium ions.
Improves the compatibility and stability of the electrode/electrolyte interface, reduces the internal resistance of the interface, improves the conductivity of the electrolyte, extends the cycle life of the battery, and improves the overall performance of the solid-state battery.
Smart Images

Figure CN114824450B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of functional electrolytes, and specifically relates to a laminated composite electrolyte with interface optimization function and a preparation method thereof. Background Art
[0002] All-solid-state lithium batteries based on inorganic solid electrolytes, high-nickel ternary oxide positive electrodes, and metal lithium negative electrodes can avoid the safety issues of liquid batteries such as natural and leakage because they do not use liquid electrolytes. In addition, due to the structural characteristics of solid electrolytes, they are easier to package and have great market prospects. However, the process of transforming from liquid electrolytes to solid electrolytes brings new challenges - interface problems: (1) The solid-solid contact between the positive and negative electrode materials and the hard oxide electrolyte is poor. Especially during the charge and discharge cycle, the decomposition of the electrode materials and the evolution of the interface phase will lead to changes in stress / strain, resulting in the formation and expansion of cracks, interface stratification, and the reduction of the overall physical connectivity between particles and components, which deteriorates the interface characteristics and battery performance; (2) The chemical stability between the positive and negative electrode materials and the hard oxide electrolyte is poor, which makes it easy for side reactions such as element diffusion and redox to occur on the interface. The above-mentioned interface problems have become a bottleneck restricting the development of solid-state batteries. Therefore, optimizing the interface is of great significance to the market application of all-solid-state batteries.
[0003] In organic-inorganic laminated composite electrolytes, organic and inorganic substances are stacked in layers, and each layer cooperates with each other, which can effectively improve the interface problems of all-solid-state batteries. However, laminated composite electrolytes increase the number of interfaces, and the interface impedance between different phases cannot be ignored. In addition, the flexible electrode / electrolyte interface is mainly based on physical interactions with low intensity, and the volume change of the material during the cycle is easy to cause the destruction of the interface structure. The key to solving the above problems of laminated composite electrolytes is to explore a substance that can chemically interact with organic and inorganic substances at the same time, and cooperate with flexible physical effects without increasing the internal resistance of the interface to achieve the joint regulation of multiple interfaces of electrode / electrolyte, organic electrolyte / inorganic electrolyte. "Molecular bridge" silane coupling agent is a special substance that has two groups with different chemical properties at the same time-silane alkoxy and alkyl chain, which can react with inorganic and organic substances respectively. Applying it to the electrolyte can form a special bonding interface, thereby regulating the organic / inorganic interface, reducing the internal resistance of the interface, and improving the performance of the composite material. In recent years, silane coupling agents have been introduced into the battery field, mainly for surface modification of positive and negative electrode materials to avoid corrosion by electrolytes; modification of inorganic nanoparticles to improve their dispersibility in organic solvents; and increase of the mechanical properties of electrolytes. However, in solid-state battery systems, the application of coupling agents mainly emphasizes the reactivity of alkoxy and alkyl chains in coupling agents to inorganic and organic substances, respectively, and the role of special functional groups is relatively lacking. The special functional groups in coupling agents have an important influence on the interfacial interaction of solid-state battery systems, which directly affects the interfacial properties and the overall performance of the entire battery system. There are many types of silane coupling agents, among which acrylamide-based silane coupling agents, because they contain highly active acrylamide groups, will have a special regulatory effect on the interfacial properties of solid-state batteries, but related research is still relatively lacking. Summary of the invention
[0004] The object of the present invention is to provide a laminated composite electrolyte with interface optimization function and a preparation method thereof to solve the technical problems mentioned in the above background technology.
[0005] To achieve the above object, the present invention provides the following technical solution: a stacked composite electrolyte with interface optimization function, comprising an organic electrolyte, an inorganic electrolyte and a silane coupling agent containing an acrylamide group.
[0006] Preferably, the silane coupling agent containing an acrylamide group is one of acrylamidopropyltrimethylsiloxysilane, (3-methacrylamidopropyl)triethoxysilane and methacryloxyaminotrimethylsilane.
[0007] Preferably, the organic electrolyte is a PEO-based electrolyte membrane, and the inorganic electrolyte is LLZAO.
[0008] A laminated composite electrolyte with interface optimization function, the preparation method of which comprises the following steps:
[0009] Step 1, adding an organic electrolyte and a lithium salt to acetonitrile, adding an acrylamide silane coupling agent, and heating and stirring at 30-60° C. for 1-2 hours;
[0010] Step 2, the solution obtained in step 1 is placed in a glove box with a water and oxygen content of less than 0.1 ppm, and mold casting and solvent evaporation are performed to prepare an acrylamide silane-modified organic electrolyte membrane;
[0011] Step 3, after adding acrylamide silane to LLZAO powder, pressing it into a disc with a diameter of 16 mm and a thickness of 100-500 μm to obtain an acrylamide silane-modified LLZAO inorganic electrolyte membrane;
[0012] Step 4, stacking the three layers of the organic electrolyte membrane, inorganic electrolyte membrane and organic electrolyte membrane obtained in steps 2 and 3 and pressurizing them to obtain a stacked functional electrolyte.
[0013] Preferably, in the preparation method, the amount of acrylamide-based silane coupling agent added is 2-100 μL, and the mass of the organic electrolyte is 500-1000 mg.
[0014] Preferably, in the preparation method, the lithium salt is one or more of LiPF6, LIClO4, LiTFSI, and LiFSI, and n (organic electrolyte): n (lithium salt) = 8-22.
[0015] A solid-state lithium battery comprises a positive electrode sheet, a negative electrode sheet and a stacked composite electrolyte with an interface optimization function.
[0016] Preferably, the positive electrode plate is coated on an aluminum foil with a conductive additive, a binder and an NCA positive electrode material, and the proportions of the three are 60-99wt.% of NCA positive electrode material, 0.5-20wt.% of binder and 0.5-20wt.% of conductive agent.
[0017] Preferably, the conductive additive is a mixture of one or more of conductive carbon black, Ketjen black ECP, conductive graphite vapor-grown carbon fiber, carbon nanotubes, and graphene; the binder is a mixture of one or more of polyvinylidene fluoride, polytetrafluoroethylene, sodium carboxymethyl cellulose, and polyvinyl alcohol.
[0018] Preferably, the negative electrode sheet is a lithium sheet.
[0019] The beneficial effects of the present invention are:
[0020] (1) Silane coupling agents can be used to chemically react with inorganic electrodes and organic electrolytes through their own silane alkoxy and acrylamide chains, respectively, and with the help of the flexible physical effect of polymers to connect electrodes and electrolytes, thereby improving interfacial compatibility and stability. In addition, during the battery charge and discharge cycle, the irreversible decomposition of electrode materials and the evolution of interfacial phases will lead to the formation and expansion of cracks, resulting in interfacial stratification and reduced physical connectivity. The excess acrylamide in the silane coupling agent will chemically adsorb on the electrode surface to form a modified layer, and can also participate in the chemical reaction of the interface, react with fresh active sites on the electrode surface to form new connections, avoid the destruction of the interfacial layer during the cycle, and thus maintain the stability and durability of the connection interface.
[0021] (2) The acrylamide-based silane coupling agent used, in addition to the function of conventional coupling agents to connect organic-inorganic interfaces, has multiple hydrogen bonds in its acrylamide, which can enrich the lithium ion environment of the battery, so that the lithium interaction force is transformed from the original single Li···OC to the coexistence of multiple lithium interactions (Li···OC, Li···NH and Li···O=C), which is beneficial to improving the conductivity of the electrolyte; the acyloxy group in the acrylamide group has a strong lithium affinity, which can regulate the diffusion behavior of lithium ions on the surface of the lithium negative electrode, uniformly deposit / dissolve lithium, prevent lithium enrichment and dendrite formation, and further improve the stability of the electrode / electrolyte interface. The above chemical reactions, combined with the flexible physical properties of the organic components on both sides of the stacked electrolyte, can effectively improve the rigid interface problem existing in the solid-state battery system. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a schematic diagram of the working principle of the layered composite electrolyte of the present invention;
[0023] Figure 2 The cycle performance curves of the comparative example 1 and the example 4 of the present invention at different numbers of cycles at 50°C are shown. DETAILED DESCRIPTION
[0024] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] When preparing the above stacked composite electrolyte, the acrylamide silane coupling agent is one or more of acrylamide propyl trimethylsiloxy silane, (3-methacrylamide propyl) triethoxy silane, and methacryloxyamine trimethyl silane, the mass of PEO is 0.5 g, and the lithium salt is n(EO):n(lithium salt)=12:1.
[0026] The method for preparing the above laminated composite electrolyte comprises:
[0027] Step 1, add PEO and lithium salt into 5 mL of acetonitrile, add acrylamide silane coupling agent, and heat and stir at 30-60° C. for 1-2 h.
[0028] Step 2: The solution obtained in step 1 is placed in a glove box with a water and oxygen content of less than 0.1 ppm, and mold casting and solvent evaporation are performed to prepare an acrylamide silane-modified PEO-based organic electrolyte membrane.
[0029] Step 3, after adding acrylamide silane to LLZAO powder, pressing it into a disc with a diameter of 16 mm and a thickness of 100-500 μm to obtain an acrylamide silane-modified LLZAO inorganic electrolyte membrane.
[0030] Step 4, stacking the three layers of the organic electrolyte membrane, inorganic electrolyte membrane and organic electrolyte membrane obtained in steps 2 and 3 and pressurizing them to obtain a stacked functional electrolyte.
[0031] The use of acrylamide-based silane coupling agents to modify stacked organic-inorganic composite electrolytes can not only play the role of coupling agents in connecting organic and inorganic substances, but also utilize the multiple hydrogen bonds of acrylamide groups to improve the environment of lithium ions and increase the conductivity of the electrolyte. In addition, the acyloxy group in the acrylamide group has a strong affinity for lithium, which can regulate the diffusion behavior of lithium ions on the surface of the lithium negative electrode, uniformly deposit / dissolve lithium, and further improve the stability of the electrode / electrolyte interface. The above chemical reactions, combined with the flexible physical properties of the organic components on both sides of the stacked electrolyte, can effectively improve the rigid interface problems existing in the solid-state battery system, thereby improving the performance of solid-state batteries.
[0032] In addition, an embodiment provides a solid-state lithium battery, including a positive electrode sheet, a negative electrode sheet, and a stacked composite electrolyte.
[0033] In an embodiment, the positive electrode plate is coated on an aluminum foil with a conductive additive, a binder and an NCA positive electrode material, and the proportions of the three are respectively 60-99wt.% of NCA positive electrode material, 0.5-20wt.% of binder, and 0.5-20wt.% of conductive agent, wherein the conductive agent additive is a mixture of one or more of conductive carbon black, Ketjen black ECP, conductive graphite vapor-grown carbon fiber, carbon nanotubes, and graphene; the binder is a mixture of one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), sodium carboxymethyl cellulose (CMC), and polyvinyl alcohol (PVA), and the negative electrode plate is a lithium plate.
[0034] Example 1
[0035] Step 1, add 0.6 g PEO and 0.25 g lithium salt into 5 mL acetonitrile, add 10 μL (3-methacrylamidepropyl) triethoxysilane coupling agent, and heat and stir at 45° C. for 1 h.
[0036] Step 2: The solution obtained in step 1 is placed in a glove box with a water and oxygen content of less than 0.1 ppm, and mold casting and solvent evaporation are performed to prepare an acrylamide silane-modified PEO-based organic electrolyte membrane.
[0037] Step 3: After adding 10 μL (3-methacrylamidepropyl)triethoxysilane to 0.1 g LLZAO powder, the mixture was pressed into a disc with a diameter of 16 mm and a thickness of 150 μm to obtain an acrylamide-silane-modified LLZAO inorganic electrolyte membrane.
[0038] Step 4, stacking the three layers of the organic electrolyte membrane, inorganic electrolyte membrane and organic electrolyte membrane obtained in steps 2 and 3 and pressurizing them to obtain a stacked functional electrolyte.
[0039] Example 2
[0040] Step 1, add 0.6 g PEO and 0.25 g lithium salt into 5 mL acetonitrile, add 20 μL (3-methacrylamidepropyl) triethoxysilane coupling agent, and heat and stir at 45° C. for 1 h.
[0041] Step 2 is the same as step 2 of Example 1.
[0042] Step 3: After adding 20 μL (3-methacrylamidepropyl)triethoxysilane to 0.1 g LLZAO powder, the mixture was pressed into a disc with a diameter of 16 mm and a thickness of 150 μm to obtain an acrylamide-silane-modified LLZAO inorganic electrolyte membrane.
[0043] Step 4 is the same as step 4 of Example 1.
[0044] Example 3
[0045] Step 1, add 0.6 g PEO and 0.25 g lithium salt into 5 mL acetonitrile, add 30 μL (3-methacrylamidepropyl) triethoxysilane coupling agent, and heat and stir at 45° C. for 1 h.
[0046] Step 2 is the same as step 2 of Example 1.
[0047] Step 3: After adding 30 μL (3-methacrylamidepropyl)triethoxysilane to 0.1 g LLZAO powder, the mixture was pressed into a disc with a diameter of 16 mm and a thickness of 150 μm to obtain an acrylamide-silane-modified LLZAO inorganic electrolyte membrane.
[0048] Step 4 is the same as step 4 of Example 1.
[0049] Example 4
[0050] Step 1, add 0.6 g PEO and 0.25 g lithium salt into 5 mL acetonitrile, add 40 μL (3-methacrylamidepropyl) triethoxysilane coupling agent, and heat and stir at 45° C. for 1 h.
[0051] Step 2 is the same as step 2 of Example 1.
[0052] Step 3, after adding 40 μL (3-methacrylamidepropyl) triethoxysilane to 0.1 g LLZAO powder, the mixture was pressed into a disc with a diameter of 16 mm and a thickness of 150 μm to obtain an acrylamide silane-modified LLZAO inorganic electrolyte membrane.
[0053] Step 4 is the same as step 4 of Example 1.
[0054] Example 5
[0055] Step 1, add 0.6 g PEO and 0.25 g lithium salt into 5 mL acetonitrile, add 50 μL (3-methylacrylamidepropyl) triethoxysilane coupling agent, and heat and stir at 45° C. for 1 h.
[0056] Step 2 is the same as step 2 of Example 1.
[0057] Step 3: After adding 50 μL (3-methacrylamidepropyl)triethoxysilane to 0.1 g LLZAO powder, the mixture was pressed into a disc with a diameter of 16 mm and a thickness of 150 μm to obtain an acrylamide-silane-modified LLZAO inorganic electrolyte membrane.
[0058] Step 4 is the same as step 4 of Example 1.
[0059] Example 6
[0060] Step 1, add 0.6 g PEO and 0.25 g lithium salt into 5 mL acetonitrile, add 60 μL (3-methacrylamidepropyl) triethoxysilane coupling agent, and heat and stir at 45° C. for 1 h.
[0061] Step 2 is the same as step 2 of Example 1.
[0062] Step 3: After adding 60 μL (3-methacrylamidepropyl)triethoxysilane to 0.1 g LLZAO powder, the mixture was pressed into a disc with a diameter of 16 mm and a thickness of 150 μm to obtain an acrylamide-silane-modified LLZAO inorganic electrolyte membrane.
[0063] Step 4 is the same as step 4 of Example 1.
[0064] Comparative Example 1
[0065] Except for the step of adding a coupling agent in steps 1 and 3, the other steps are the same as those in the embodiment.
[0066] 80wt.% NCA positive electrode material, 15wt.% conductive agent carbon black and 5wt.% binder PVDF were made into slurry and coated on aluminum foil, and then vacuum dried at 80°C and cut into 12mm positive electrode sheets. In a glove box, button cells were assembled, in which the above-mentioned electrode sheet was used as the positive electrode, the lithium sheet was used as the negative electrode, and the electrolyte membrane was the electrolyte membrane prepared above.
[0067] As can be seen from the figure, the charge and discharge test was carried out at 50°C, 0.1C rate, and 3.0-4.3V. The battery in Example 4 had a discharge capacity of about 201.3mAh / g in the first week, and after 100 cycles, the capacity was about 171.1mAh / g, with a capacity retention rate of up to 85%; while the battery in Control Example 1 had a discharge capacity of about 196.4mAh / g in the first week, and after 80 cycles, the capacity had decayed to 109.1mAh / g, and the battery failed. It can be seen that after adding acrylamide coupling agents, the cycle life of the battery is significantly improved.
[0068] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A laminated composite electrolyte with interface optimization function, characterized in that: The laminated composite electrolyte with interface optimization function comprises an organic electrolyte, an inorganic electrolyte and a silane coupling agent containing an acrylamide group; The preparation method thereof comprises the following steps: Step 1, adding an organic electrolyte and a lithium salt to acetonitrile, adding an acrylamide silane coupling agent, and heating and stirring at 30-60° C. for 1-2 hours; Step 2, the solution obtained in step 1 is placed in a glove box with a water and oxygen content of less than 0.1 ppm, and mold casting and solvent evaporation are performed to prepare an acrylamide silane-modified organic electrolyte membrane; Step 3, after adding acrylamide silane to LLZAO powder, pressing it into a disc with a diameter of 16 mm and a thickness of 100-500 μm to obtain an acrylamide silane-modified LLZAO inorganic electrolyte membrane; Step 4, stacking the three layers of the organic electrolyte membrane, inorganic electrolyte membrane and organic electrolyte membrane obtained in steps 2 and 3 and pressurizing them to obtain a stacked functional electrolyte.
2. The laminated composite electrolyte with interface optimization function according to claim 1, characterized in that: The silane coupling agent containing acrylamide groups is one of acrylamidopropyltrimethylsiloxysilane, (3-methacrylamidepropyl)triethoxysilane and methacryloxyaminotrimethylsilane.
3. The laminated composite electrolyte with interface optimization function according to claim 2, characterized in that: The organic electrolyte is a PEO-based electrolyte membrane, and the inorganic electrolyte is LLZAO.
4. The laminated composite electrolyte with interface optimization function according to claim 1, characterized in that: In the preparation method, the added amount of acrylamide-based silane coupling agent is 2-100 μL, and the mass of the organic electrolyte is 500-1000 mg.
5. The laminated composite electrolyte with interface optimization function according to claim 4, characterized in that: In the preparation method, the lithium salt is one or more of LiPF6, LIClO4, LiTFSI, and LiFSI, and the molar ratio of the organic electrolyte to the lithium salt is 8-22.
6. A solid-state lithium battery, characterized in that: The invention comprises a positive electrode sheet, a negative electrode sheet and a laminated composite electrolyte with interface optimization function as claimed in any one of claims 1 to 3.
7. The solid-state lithium battery according to claim 6, characterized in that: The positive electrode plate is coated on an aluminum foil with a conductive additive, a binder and an NCA positive electrode material, wherein the proportions of the three are 60-99 wt.% of the NCA positive electrode material, 0.5-20 wt.% of the binder and 0.5-20 wt.% of the conductive agent.
8. The solid-state lithium battery according to claim 7, characterized in that: The conductive additive is a mixture of one or more of conductive carbon black, Ketjen black ECP, conductive graphite, vapor-grown carbon fiber, carbon nanotubes, and graphene; the binder is a mixture of one or more of polyvinylidene fluoride, polytetrafluoroethylene, sodium carboxymethyl cellulose, and polyvinyl alcohol.
9. The solid-state lithium battery according to claim 7, characterized in that: The negative electrode sheet is a lithium sheet.
Citation Information
Patent Citations
Composite solid electrolytes for high-performance metallic or metal-ion batteries
US20210226247A1